#TITLE_ALTERNATIVE# - Danas Okvendrajaya (NIM 122 03 009), Radhintya
Abstract: Skin factor is one phenomena of flow restriction which is commonly found in the production wells, either oil wells or gas wells. According to its component, there are four types of skin factor, which are skin damage, perforation skin, skin due to non-Darcy flow, and skin depending on the flow rate and time. The sum of those components indicates the total skin factor. This research is focused on one of the total skin factor components, which have been described above, that is the flow rate and time - dependent skin, commonly known as S(q, t). This type of flow restriction usually occurs on wells producing from solution gas drive reservoirs, also on condensate reservoirs. For an oil reservoir, where the reservoir pressure still remains above the bubble point pressure, the gas saturation is equal to zero since, the gas phase has not been liberated from the oil phase. At these conditions, where the reservoir pressure is below the bubble point pressure, the gas phase will start to be liberated and accumulate until the critical gas saturation is reach. The presence of gas, which is unable to flow, will produce oil flow restriction, which is called skin factor, and represented by S(q,t). S(q,t) does not occur at all the life time of production, it only occurs at some certain period where the gas saturation start to form, until the gas saturation at the whole reservoir is greater than the critical gas saturation. The growth of S(q,t) is the main topic in this research, by considering the rate and time factors. Based from this research, the influence of production rate to S(q,t) is showed that at higher rate, the maximum value of S(q,t) will also be higher but in the other hand, the occurrence will emerge in a shorter time period. Although it affects only at some certain time period, it is a must to observe the growth behavior of S (q,t) and all the parameters that influence the occurrence of this type of skin factor. It is important in the production well planning, especially at an oil reservoir which has the initial reservoir pressure greater than the bubble point pressure